Safety of accessing brachial veins for large-bore upper extremity venous thrombectomy using ClotTriever Thrombectomy System - Luke A. Verst; Colvin Greenberg; David S. Shin; Matthew Abad-Santos; Eric J. Monroe; Mina S. Makary; Jeffrey Forris Beecham Chick (CVIR Endovascular)
Abstract Purpose To evaluate access site adverse events following ClotTriever-mediated large-bore mechanical thrombectomy via small upper extremity deep veins (< 6-mm). Materials and methods Twenty patients, including 24 upper extremity venous access sites, underwent ClotTriever-mediated large-bore thrombectomy of the upper extremity and thoracic central veins for symptomatic deep vein obstruction unresponsive to anticoagulation. Patients without follow-up venous duplex examinations (n = 3) were excluded. Patients who had > 6-mm diameter veins accessed (n = 3) were excluded. Temporary purse-string sutures and manual pressure were used for access site hemostasis in all patients. Vein access site and diameter, technical success (defined as placement of the 13.5-French ClotTriever sheath followed by thrombectomy), and early (< 30-days) and late (> 30-days) access site-related adverse events (according to the Adverse Event Classification by the Society of Interventional Radiology criteria) were recorded. Results Fourteen patients (8 males, 6 females; mean age 51.7 ± 13.6 years) comprising 16 upper extremity venous access sites were included in this study. Access sites included: right brachial (n = 7), left brachial (n = 5), and bilateral brachial (n = 2) veins. The mean access site diameter was 4.3-mm ± 0.67-mm. Technical success was achieved via all access sites. Six (42.9%) patients underwent stent reconstruction following thrombectomy through the same accesses. After the procedure, all purse-string sutures were removed within 24 h. Three (21.4%) patients experienced small access site hematomas that did not require transfusion, intervention, or prolonged hospitalization. Initial follow-up venous duplex ultrasounds were performed at 29.3 ± 21.7 days following intervention. The mean follow-up interval to the second and third venous duplex ultrasounds were 124.3 ± 64-days and 225.1 ± 80.1 days, respectively. One (7.1%) patient developed right arm swelling six days after the procedure and was found to have thrombosis of the previously accessed right brachial vein. No other clinically or sonographically significant access site adverse events were observed. Conclusion ClotTriever-mediated large-bore thrombectomy via small upper extremity veins is safe with minimal access site adverse events.